Socio-behavioural and structural core drivers of new HIV infection as perceived by employees at Department of Agriculture in Mopani District, Limpopo Province - Mathebula, Thandy Shirley (My University, 2018)
Despite the laudable progress on HIV and AIDS interventions encountered in South Africa, new HIV infection remains a challenge. Limpopo Department of Agriculture is not an exception as far as new HIV infections are concerned, regardless of the intervention efforts made. This study aimed at exploring on perceptions of LDA employees on social-behavioural and structural core drivers of HIV infection. Qualitative research methodologies were applied. A purposive sample of twenty participants (10 men and 10 women) was selected from Department of Agriculture, Mopani District, Limpopo Province. Constructivism and structuralism theoretical framework were used to navigate the study. Semi-structured, face-to-face interviews were designed. Data was collected through interviews, audio-recorded and transcribed. Eight steps of data analysis were followed as proposed by Creswell. Guidelines for the prevention of new HIV infection were developed. Some of the major findings are that: the socio-behavioural core drivers that place all partners at risk of contracting new HIV infections is the Multiple Sexual Partnerships (MSPs). Age-disparate relationships in a workplace were also socio-behavioural drivers of new HIV infection. Young women and men who enter into age-disparate relationships have intention of obtaining permanent employment. Patriarchy was found to be amongst the structural core drivers of new HIV infections. The fact that men are not tested involuntarily is viewed as a structural barrier towards eliminating the spread of new HIV infections. Stigma has been also found to be a core driver of new HIV infections. Some conclusions made are: MSPs is a closed sexual network system, characterised by “secrecy” and “trust”. Despite some reforms purporting to improve women’s status, patriarchal domination is still at its toll. Unsymbolised stigma remains a threat towards elimination of the spread of HIV infections. The major recommendations are that working women still require empowerment in number of areas of their social functioning, and the leadership involvement in the fight against the spread of new HIV infections.
Thesis (Ph. D. (Social Work)) --University of Limpopo, 2018
Keywords: HIV and AIDS; Limpopo Department of Agriculture; New HIV infections; 362.1969; Communicable diseases; HIV-positive persons; HIV (virus)